2019
DOI: 10.29103/ijevs.v1i7.1675
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students Learning Outcomes Through Mind Map in Human Reproductive System Topic in Natural Science Learning

Abstract: Natural science learning on the topic of the human reproductive system still gets a low score. That is due to the lack of use of learning media. The purpose of this study is to improve student learning outcomes through the use of mind maps in the topic of the human reproductive system. The research method used was classroom action research with the stages of pre-cycle, cycle 1, and cycle 2. The study was conducted in July 2019 and carried out at State Junior High School 1 South Tambun, Bekasi, Indonesia. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Mind mapping activities both individually and in groups require students to be able to understand and remember the material they read, then express it in writing (Muslimin, 2019). The use of mind map media will make it easier for students to understand topics with high conceptual complexity (Dewi, 2019). Some learners still have a medium in practicing mind mapping worksheet during learning have not shown creative thinking skills, and the results of the mind map cells made are not in accordance with the correct instructions.…”
Section: Mind Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mind mapping activities both individually and in groups require students to be able to understand and remember the material they read, then express it in writing (Muslimin, 2019). The use of mind map media will make it easier for students to understand topics with high conceptual complexity (Dewi, 2019). Some learners still have a medium in practicing mind mapping worksheet during learning have not shown creative thinking skills, and the results of the mind map cells made are not in accordance with the correct instructions.…”
Section: Mind Mappingmentioning
confidence: 99%
“…The effectiveness of genetics worksheets to train creative thinking skills using one group pre-post test design shows the development of students' creative thinking skills (Susanti et al, 2016). Mind mapping method in learning the human reproductive system in junior high school students, improves student learning outcomes and student responses are very helpful in remembering for understanding Latin languages and new concepts in the material (Dewi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Students in delivering results must maintain the reasons for the solutions that have been offered so that problem-solving skills in indicators of maintaining solutions can be improved. Group activities in analyzing problems, discussing options, making decisions, and reporting in front of the class in solving problems based on real learning situations will improve problem-solving skills (Simone, 2014;Ristiasari et al, 2012;Fatmawati, 2016;& Dewi, 2019). The research faced an obstacle: students' lack of skill in developing a solution to problems found.…”
Section: Figurementioning
confidence: 99%
“…A type of inquiry model, other learning models belonging to the cooperative model also provide effective learning outcomes (Irfanto et al, 2019). In addition, according to Dewi (2019), one other method that is able to provide ease of learning is the Mind Map, because it provides a concept mind map for students to understand. Wahyuni et al (2020); and Widiantoro et al (2020) comparing learning outcomes with the direct learning model showed significant results, the Problem-Based Learning model also had a positive influence on student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%